Gestion administrativa y financiera y su incidencia en la rentabilidad de la distribución lácteos A.R.C.C. Cantón Quevedo periodo 2012 – 2014 - Zambrano Bohórquez, María Mariuxi (2016)
This research was conducted at the Dairy Distribuidora ARCC for the purpose of analyzing the administrative and financial management and its impact on profitability 2012-2014 period. A diagnosis of the situation of Distribuidora ARCC was conducted to determine the causes and effects of the problem, clearly it defined objectives for the development of the research project. His theoretical framework is based on various definitions and concepts related to the topic studied authors. Its legal basis is based on state laws and regulations that allow the proper functioning in the administrative and financial areas of the company. As methodology deductive, inductive and analytical method was used, developing a field research, documentary and descriptive, choosing the technique of interview and survey using questionnaires applying them to all the people that make up the Distributor. As anticipated research results which administrative processes running the Distributor for the development of its activities are determined, an analysis of its financial statements was performed using the financial indicators of liquidity, indebtedness, working capital and profitability, defined each of its economic to know which of these activities are profitable or not and what administrative and financial strategies should be implemented within the company which in turn contribute to decision making.